S-BPM ONE - application studies and work in progress : 6th International Conference, S-BPM ONE 2014, Eichstätt, Germany, April 22-23, 2014. Proceedings - Zehbold, Cornelia (Communications in Computer and Information Science, 2014)
This book constitutes the thoroughly refereed proceedings of the 6th International Conference on Subject-Oriented Business Process Management, S-BPM ONE 2014, held in Eichstätt, Germany, in April 2014. The 14 application-oriented papers selected during the peer review process and included in this volume deal with a variety of topics ranging from model elicitation over strategic alignment to the application of S-BPM in different domains like software effort estimation, production planning and education.